Controlling the Unemployment Rate in South Sulawesi Province through Economic Growth, Provincial Minimum Wage and Inflation - Murtiadi Awaluddin; Ilham Ilham; Mutakallim Sijal; Andi Sylvana (EcceS (Economics, Social, and Development Studies), 2021)
Unemployment in South Sulawesi is very worrying and quite disturbing economic performance in this area. Although the government has made efforts to achieve growth based on employment and increase the minimum wage, conditions have not been able to reduce the unemployment rate itself. The novelty of this research is to try to dig deeper into the interrelationship of minimum wage setting policies, efforts to increase economic growth and efforts to control inflation by the government, to the unemployment phenomenon that occurs in South Sulawesi Province. This study aims to determine how the influence of economic growth, the provincial minimum wage and inflation on unemployment in South Sulawesi Province, Indonesia in 2005-2019. The type of research used is quantitative, namely the research method which is a scientific approach to economic decisions by using multiple linear regression analysis to find out how much influence the variables studied are. The results show that simultaneously economic growth, provincial minimum wages and inflation have a significant effect on unemployment in South Sulawesi Province. Partially, economic growth and provincial minimum wages have a significant negative effect on unemployment in South Sulawesi Province. Meanwhile, inflation has a positive and insignificant effect on unemployment in South Sulawesi Province. The implication of this research is that the government needs to increase quality and more inclusive economic growth based on expanding job opportunities and increasing human capital.Keywords: Unemployment; Economic Growth; Minimum Wage; Inflation